2019
DOI: 10.1038/s41598-019-44595-4
|View full text |Cite
|
Sign up to set email alerts
|

CSN5 inhibition triggers inflammatory signaling and Rho/ROCK-dependent loss of endothelial integrity

Abstract: RhoGTPases regulate cytoskeletal dynamics, migration and cell-cell adhesion in endothelial cells. Besides regulation at the level of guanine nucleotide binding, they also undergo post-translational modifications, for example ubiquitination. RhoGTPases are ubiquitinated by Cullin RING ligases which are in turn regulated by neddylation. Previously we showed that inhibition of Cullin RING ligase activity by the neddylation inhibitor MLN4924 is detrimental for endothelial barrier function, due to accumulation of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…2B, fig. S3E), which can sometimes run lower than its predicted molecular weight (25). Therefore, we tested if cullin1 neddylation is altered upon CSN5 knockdown, and found that knockdown cells accumulated neddylated cullin1 by immunoblot analysis using antibodies specific for E. histolytica cullin1 and Nedd8 (Fig.…”
Section: Cop9 Signalosome Is Necessary For Parasite Protein Degradationmentioning
confidence: 99%
“…2B, fig. S3E), which can sometimes run lower than its predicted molecular weight (25). Therefore, we tested if cullin1 neddylation is altered upon CSN5 knockdown, and found that knockdown cells accumulated neddylated cullin1 by immunoblot analysis using antibodies specific for E. histolytica cullin1 and Nedd8 (Fig.…”
Section: Cop9 Signalosome Is Necessary For Parasite Protein Degradationmentioning
confidence: 99%
“…histolytica cullin1 protein (EHI_118180) [ 32 ] which has the conserved neddylation site ( S4 Fig ). Immunoblot analysis revealed the most intense neddylated band after CSN5 disruption being above the 75 KDa mark, which includes neddylated cullin1 ( Fig 2B , S3E Fig and S6D Fig ), which can sometimes run lower than its predicted molecular weight [ 48 ]. Therefore, we tested if cullin1 neddylation is altered upon CSN5 knockdown, and found that knockdown cells accumulated neddylated cullin1 by immunoblot analysis using antibodies specific for E .…”
Section: Resultsmentioning
confidence: 99%
“…The state-of-art research has proven that treatment of human umbilical vein endothelial cells with a COP9 signalosome inhibitor (pharmacological activation of CRLs) enhanced intercellular cell adhesion molecule (ICAM) expression and resulted in consequent adhesion of neutrophils to endothelial cells. 55 Moreover, the glioma cells after MLN4924 treatment were reported to have a stronger potential to induce T-cell anergy. 56 Recently, our colleagues uncovered that neddylation inactivation in tumor cell increased C-C motif chemokine ligand 2 (CCL2) secretion and then promoted tumor-associated macrophage infiltration.…”
Section: Neddylation In Other Cellsmentioning
confidence: 99%
“…In a consequence, typical targets for NF-κB such as proinflammatory cytokines (TNF-α, IL-6), chemokines (CCL2/MCP1), antirival factor (IFN-β) and adhesion molecules (ICAM) are downregulated. 25,55,57,65 However, what's puzzling is that neddylation inactivation usually promotes the accumulation of phosphorylated IκBα, rather than total IκBα, in some studies. 34,66 It may be interpreted that other protein degradation pathways are involved in the regulation.…”
Section: Neddylation-modulated Signaling Molecule In the Immune Resmentioning
confidence: 99%
See 1 more Smart Citation